Path of intuitive compassion to transform conflicts into enduring peace and prosperity: Symmetry across domains of reiterated prisoner's dilemma, dyadic active inference, and Mahayana Buddhism - Ho, S. Shaun; Nakamura, Yoshio; Swain, James E. (Frontiers in Psychology, 2023)
As the meme of “life is a battle of us the good vs. them the evil” proliferates in many communities, conflicts are increasingly intensified among the members of community—making it almost impossible to extend compassion—defined as a wish to relieve others from suffering—from one side to the other. Is compassion even relevant to conflicts? The answer depends on how a conflict is framed in one’s perception. If a conflict is perceived in a frame of zero-sum competition, then compassion is meaningless in such a “tug-of-war” mindset. Conversely, if perceived in a non-zero-sum frame—as demonstrated in reiterated prisoner’s dilemma (rPD) in which two players may interdependently render win-win, lose-lose, win-lose, or lose-win scenarios by their actions—then compassion can help achieve the most preferable outcomes for all in a “dyadic dance” mindset. In this paper, we present a path of intuitive compassion by pointing to symmetry across three distinct domains of rPD, dyadic active inference, and Mahayana Buddhism. In each of these domains, conflicts serve as points of bifurcation on a bi-directional path and compassion as a conflict-proof commitment to carrying out the best strategies—even if assessed for one’s own sake only—that consistently produce optimal payoffs in rPD, minimal stress in dyadic active inference, and limitless joy of ultimate enlightenment in Mahayana Buddhism. Conversely, lack of compassion is caused by invalid beliefs that obscure the nature of reality in these domains, causing conflicts to produce even more conflicts. These invalid beliefs are produced by mistakes of over-reduction, over-separation, and over-compression in the mind and therefore a person’s mindset is overly compressed from a multi-dimensional frame to a one-dimensional one. Taken together, intuitive compassion is not about how to balance one’s self-serving goals with altruistic ones. Rather, it is a conflict-proof commitment to transforming conflicts into enduring peace and prosperity according to the ultimate nature of reality. The work presented here may serve as a preliminary science-informed introduction to a genre of time-tested compassion meditations, i.e., lojong mind training, for the world laden with conflicts, starting from the conflicts in close relationships to those in geopolitics.